PENGARUH BRAND IMAGE DAN KUALITAS PRODUK TERHADAP KEPUASAN DAN LOYALITAS PELANGGAN MOBIL HILUX DI KABUPATEN MERAUKE - Muhammad Awal; Dian Parawansa; Jumidah Maming (Master of Management, Faculty of Economics and Business, Hasanuddin University., 2018)
Developments in the business world in Indonesia is very rapid, the challenges that will be faced by business people will be more difficult. This study aims to know to know the effect of Brand Image and Product Quality to Satisfaction and Customer Loyalty Hilux Car in Merauke District. This research uses quantitative method. In this research use path analysis model because of independent variable with dependent variable to mediation that influence. This analysis is assisted by SPSS 22.0 software. Test results have been done indicate that Brand Image positively and significantly influence on satisfaction, product quality positively and significantly influence on satisfaction, Brand Image positively and significantly influence on Customer Loyalty, Product quality positively and significantly influence to customer loyalty, Satisfaction positively and significantly influence customer loyalty.